Effect of lithium chloride on cell proliferation and osteogenic differentiation in stem cells from human exfoliated deciduous teeth. Issue 5 (October 2016) - Rattanawarawipa, Panarat; Pavasant, Prasit; Osathanon, Thanaphum; Sukarawan, Waleerat
Highlights: LiCl attenuates SHED cell proliferation as shown by the reduction of colony formation and decrease in the percentage of cells in the sub G0 phase. LiCl significantly inhibited osteogenic marker, OSX and DMP1, mRNA expression in SHEDs. No influence of LiCl was observed on the expression of the other osteogenic marker genes, the ALP activity and mineral deposition of SHED. Abstract: Lithium Chloride (LiCl) has been used as a canonical Wnt pathway activator due to its ability to inhibit a glycogen synthase kinase-3. The aim of the present study was to investigate the effect of LiCl on cell proliferation and osteogenic differentiation in stem cells isolated from human exfoliated deciduous teeth (SHEDs). SHEDs were isolated and cultured in media supplemented with LiCl at 5, 10, or 20 mM. The results demonstrated that LiCl significantly decreased SHEDs colony forming unit ability in a dose dependent manner. LiCl significantly enhanced the percentage of cells in the sub G0 phase, accompanied by a reduction of the percentage of cells in the G1 phase at day 3 and 7 after treatment. Further, LiCl markedly decreased OSX and DMP1 mRNA expression after treating SHEDs in an osteogenic induction medium for 7 days. In addition, no significant difference in alkaline phosphatase enzymatic activity or mineral deposition was found. Together, these results imply that LiCl influences SHEDs behavior.